Біометрична автентифікація у мобільних телефонах на прикладі ємнісного методу автентифікації за відбитком пальця - Морозов, О. Ю. (ХНУРЕ, 2020)
The subject of research was to show the most popular mechanisms of biometrical authentication in mobile devices and applications. The main advantages, properties and where it can be used were presented in work.
Keywords: авторизація; автентифікація; ємнісний метод; відбиток пальця